METODE PENANGGULANGAN DISTORSI PADA SAMBUNGAN PENGELASAN GMAW UNTUK PADUAN LOGAM BAJA SEBAGAI BAHAN KONSTRUKSI BAGIAN FLOOR VESSEL PENGANGKUT BATU BARA - Lukas Febri Andreas Hutagalung (2023)
Distortion is an unwanted effect of welding. Distortion is the deformation of the workpiece after the welding process which results in the dimensions of the workpiece not conforming to the original design. Distortion can occur because the heat generated during the welding process is too large and the distribution is uneven. Distortion can be minimized by several methods, with the aim of getting the shape and size of the product according to the design. This research is a study to find out which method is the most effective in minimizing the effect of distortion in welding SS 400 alloy steel with GMAW and what is the impact of different welding methods on the tensile strength of the material. Variations in the parameters specified include methods to minimize distortion, preheat temperature and distortion effects that occur on the SS 400. Distortion measurements will be carried out with a digital protractor and ruler. The purpose of this study was to determine whether the STT and clamping methods were able to reduce distortion in SS 400 alloy steel and determine the impact on the tensile strength of the material. The hope of this research is to find out how effective the method is to reduce distortion, its impact on tensile strength and also to provide guidelines to the manufacturing industry regarding methods to reduce welding distortion in SS 400 steel alloys. Keyword : Clamping, Distortion, STT